Банановое убийство: роман / Г.М Куликова - Куликова Галина Михайловна (Астрель, 2007)
Экземпляры: ф.23 (2007) / Инвентарный номер: 51652 / Цена: / Сис.шифр: 84(2Рос=Рус)6-4 / Авт.знак: К 90 / ГРНТИ: 17.82.31 / ББК: 84(2Рос=Рус)6-44